Update on surveillance in Von Hippel-Lindau disease - Rednam, Surya; Becktell, Kerri D.; Villani, Anita; Brodeur, Garrett M.; States, Lisa J.; Doria, Andrea S.; Kamihara, Junne; Schneider, Kami Wolfe; Voss, Stephan D.; Widjaja, Elysa; Zelley, Kristin; Nakano, Yoshiko; et al. (Clinical cancer research, 2025)
Von Hippel-Lindau disease (VHL) is a genetic condition characterized by a high lifetime risk for tumors and cysts throughout the body, including the central nervous system, visual-auditory systems, and intra-abdominal organs. This neoplasia leads to significant morbidity and potential mortality in affected individuals. Tumor surveillance enables early intervention and leads to improved clinical outcomes. Since the 2017 publication of VHL tumor surveillance recommendations from the inaugural American Association for Cancer Research Childhood Cancer Predisposition Workshop, several other groups have proposed alternative consensus surveillance recommendations. Although these screening paradigms share some common elements, they also deviate from each other in some substantial ways. Clinical data continue to accrue in VHL, allowing the condition to be better characterized. Furthermore, surgical techniques have improved over time, and the option of targeted medical therapy has emerged for individuals with VHL. It is critical that surveillance strategies continue to be refined. In this perspective, we provide an up-to-date clinical overview of VHL, describe recently proposed tumor screening regimens, and finally present our updated consensus tumor surveillance recommendations during childhood and adolescence from the 2023 American Association for Cancer Research Childhood Cancer Predisposition Workshop.
Veröffentlicht: 13. Juni 2025
Gesehen am 29.10.2025